Evaluation of nonlinear Iterative methods on pipe network // Evaluación de métodos iterativos no lineales en redes de tuberías - da Silva Teixeira, Guilherme; Vilalta Alonso, Guillermo; Mendes N, Lourival J (Ingeniería Mecánica. Revista electrónica. ISSN 1815-5944, 2021)
Abstract The analysis and design of pipe networks is usually a very complex task and depending of many factors. The paper here presented explores issues related to the accuracy and robustness of three iterative nonlinear methods used for designing pipe networks: Hardy Cross method, Gradient method and Newton-Raphson method. The last two methods are implemented in EPANET and Matlab, through the fsolve function. In order to evaluate the performance of each numerical method, three pipe networks, were assessed. No differences in the results were found by using fsolve (of MatLab) and Hardy-Cross methods. However, the EPANET results show differences up to 115% regarding other two methods. This behavior can be explained by the magnitude of head loss and the flow rate in some tubes of the network with errors close to the errors set up and by the Nodal Newton-Raphson method used at EPANET’s code. The Hardy Cross method proved to be robust on three evaluated cases Key words: nonlinear methods, pipe network; EPANET; Hardy Cross method; Newton–Raphson technique.